Atomic oxygen and hydrogen loss coefficient on functionalized polyethylene terephthalate, polystyrene, and polytetrafluoroethylene polymers. Issue 9 (17th May 2018) - Zaplotnik, Rok; Vesel, Alenka; Mozetič, Miran
Abstract : Coefficients for atomic loss of hydrogen and oxygen atoms on polyethylene terephthalate (PET), polystyrene (PS), and polytetrafluoroethylene (PTFE) are determined. Measurements are performed in a flowing afterglow with different atom densities between 6 and 60 × 10 20  m −3 and in the pressure range between 8 and 200 Pa. The loss coefficients do not depend significantly on the atom density or pressure. For H atoms they are (2.3 ± 0.4) × 10 −3, (1.5 ± 0.4) × 10 −3, and (8.0 ± 3.0) × 10 −4 for PET, PS, and PTFE, respectively, whereas for O‐atoms they are (2.4 ± 1.2) × 10 −3, (2.2 ± 1.2) × 10 −3, and (1.1 ± 0.6) × 10 −3 for PET, PS, and PTFE, respectively. These values are valid after saturation of surfaces with particular atoms. Abstract : Surface loss probability for H and O atoms on PET, PS, and PTFE polymer are determined. The lowest probability is found for PTFE. Probabilities for PET and PS are of the order of 10 −3 for both gases, whereas for PTFE it is twice lower.